Analisis SWOT Pengembangan Usahatani Jeruk Manis di Desa Barung Kersap Kecamata Munthe Kabupaten Tanah Karo - Azwana Azwana; Sri Ariani Safitri; Devi Mei Yanti Tambunan (Mahesa Research Institute, 2024)
The research aims to determine the internal and external factors that influence and determine strategies for developing sweet orange farming in Barung Kersap Village. The research uses qualitative SWOT analysis techniques. The results of the research show that there are 4 internal factors Strength, namely easy to obtain agricultural inputs, high quality sweet oranges, long experience of farmers, availability of capital, with 4 weaknesses namely low level of farmer education. , There is no recording of farming activities, Fruit management is less than optimal, Sweet orange production is low. There are 3 external factors Opportunities, namely the potential for land suitable for farming, the establishment of relationships with stakeholders, the support of farmer groups, with 3 Threats, namely the development of pests and plant diseases, the decline in purchasing power and the presence of unfavorable climate/weather. regular.Based on the SWOT analysis, the strategy for developing sweet orange farming in Barung Kersap Village can be carried out using a Turn Around strategy or a WO (Weakness and Opportunities). The strategy for developing sweet orange farming business can be done by a) Increasing sweet orange production by optimizing land use (W4, O1), b) Carrying out good and correct management of orange fruit by conducting learning with farmer groups (W3, O3), c) Carrying out recording farming activities to evaluate production results by utilizing support from farmer groups (W2, O3) and d) Establishing relationships with stakeholders to increase production (W4, O2)